The Application of a Humanistic Approach in Poetry Learning that Supports Students' Mental Health - Candra, Monica Septya Kartika; Muhammad Mahyan Masbuby (Proceeding International Conference on Education, 2025)
This research aims to investigate the application of the humanistic learning approach in poetry materials in Indonesian language subjects as a means of enhancing the mental health of high school students. The research method used is descriptive qualitative. The subjects in this study were grade X students of SMA Negeri 3 Kediri, with a case study approach to two specifically selected students. To collect data, this study employed documentation techniques, specifically by collecting the results of student assignments, interviews, and questionnaires in the form of completed questionnaires. The results of processing questionnaire data from aspects that can explain the role of poetry learning and teachers in implementing a humanistic approach that supports students' mental health include, (1) Poetry functions as a medium for students' emotional expression, obtaining an average score of 18 which is categorized as high agreement, (2) Psychological safety in learning obtained an average score of 18 which is categorized as high agreement, (3) Validation of students' emotions as a psychopedagogical intervention obtained an average score of 20 which is categorized as very high agreement, (4) Emotional support and symbols of closeness between teachers and students obtained an average score of 19.5 which is categorized as very high. Overall, the humanistic approach applied by teachers obtained an average score of 19.5, which is categorized as very high. In this case, the application of a humanistic approach in poetry learning has succeeded in providing a positive impact on students' mental health.